A Theoretical Framework for the Calculation of Hausdorff Measure — Self-Similar Set Satisfying OSC (Analysis in Theory and Applications, 2011)
A theoretical framework for the calculation of Hausdorff measure of self-similar sets satisfying OSC has been established.
Keywords: Haudorff measure; open set condition.